Medical Devices Readiness in Private Outpatient Care Facilities in Riyadh within the Saudi Healthcare System - Alhussaini, Khalid; Qasim, Abdullah; Alwasel, Abdullatif; Aleid, Adham; Javed, Ravish (British Journal of Healthcare and Medical Research, 2022)
A significant transformation is observed in the Saudi healthcare system in response to the Saudi 2030 vision. Outpatient Care Facilities (OCF) are expected to carry more duties in providing healthcare services. The current study aims to analyze the readiness of medical devices in private outpatient care facilities (OCFs) in Riyadh. An on-site questionnaire-based study was conducted to assess medical equipment maintenance and its readiness in private OCFs in different regions of Riyadh, Saudi Arabia. A questionnaire was formulated following local and international guidelines and standards. The response rate to the study was 100%. Types of OCF were classified into general and specialized polyclinics, medical clinics, laboratories, and physiotherapy centers. The results of the questionnaire reveal that only 29.2% OCF have a medical device maintenance department, a periodic preventive maintenance protocol was present in 54.2% OCF, and only 12.5% OCF inspect their medical devices regularly. A lack of essential medical equipment maintenance practices was observed in the private OCF in Riyadh. Private OCF should comply with best practices in medical equipment rather than ignore Original Equipment Manufacturer (OEM) instructions, and local and international medical device maintenance guidelines. Private OCFs in Riyadh should restructure their medical equipment practices.